The image of environmental harm in American social documentary photography - Balaschak, Chris, author.
1 online resource (x, 156 pages)
Keywords: "With an emphasis on photographic works that offer new perspectives on the history of American social documentary, this book considers a history of politically engaged photography that may serve as models for the representation of impending environmental injustices. Chris Balaschak examines histories of American photography, the environmental movement, as well as the industrial and post-industrial economic conditions of the United States in the twentieth century. With particular attention to a material history of photography focused on the display and dissemination of documentary images through print media and exhibitions, the work considered places emphasis on the depiction of communities and places harmed by industrialized capitalism. The book will be of interest to scholars working in art history, visual studies, photography, ecocriticism, environmental humanities, media studies, culture studies and visual rhetoric"--